"PENENTUAN LIMIT DIAMETER TEBANG PILIH BERDASARKAN KRITERIA TINGGI ANAKAN DAN FAKTOR EKONOMIS" - Hariyatno Dwiprabowo (Jurnal Penelitian Hasil Hutan, 1990)
Indonesia  Selective Cutting System (TPI, nowTPTI) is the most widely applied  management regime in harvesting Indonesian tropical forests. It is observed that selective   cutting has created space and  canopy openings in the forest which  stimulate the growth of  seedlings and saplings of meranti species (Shorea  spp).  A study  was conducted to examine the relationship between the  seedlings  height  with  basal  area  of  trees  in several  sample  plots in logged-over forests. The relationship expressed in regression  equation then was  used  to  relate the  seedlings height to  the  cutting  diameter limit.As determination of cutting diameter limit  leads to important decision in the selective cutting,  a problem  of findine the optimal diameter limit  which maximizes the seedlings  height constrained with economic  factor  is formulated   by using nonlinear  programming.